Oscillations in cerebral haemodynamics in patients with falciparum malaria. - Kolyva, C; Kingston, H; Tachtsidis, I; Mohanty, S; Mishra, S; Patnaik, R; Maude, R; Dondorp, A; Elwell, C (2013)
Spontaneous oscillations in cerebral haemodynamics studied with near-infrared spectroscopy (NIRS), become impaired in several pathological conditions. We assessed the spectral characteristics of these oscillations in 20 patients with falciparum malaria admitted to Ispat General Hospital, Rourkela, India. Monitoring included continuous frontal lobe NIRS recordings within 24 h of admission (Day 0), together with single measurements of a number of clinical and chemical markers recorded on admission. Seven patients returned for follow-up measurements on recovery (FU). A 2,048 sampling-point segment of oxygenated haemoglobin concentration ([ΔHbO(2)]) data was subjected to Fourier analysis per patient, and power spectral density was derived over the very low frequency (VLF: 0.02-0.04 Hz), low frequency (LF: 0.04-0.15 Hz) and high frequency (HF: 0.15-0.4 Hz) bands. At Day 0, VLF spectral power was 21.1 ± 16.4, LF power 7.2 ± 4.6 and HF power 2.6 ± 5.0, with VLF power being statistically significantly higher than LF and HF (P < 0.005). VLF power tended to decrease in the severely ill patients and correlated negatively with heart rate (r = 0.57, P < 0.01), while LF power correlated positively with aural body temperature (r = 0.49, P < 0.05). In all but one of the patients who returned for FU measurements, VLF power increased after recovery. This may be related to autonomic dysfunction in severe malaria, a topic of little research to date. The present study demonstrated that application of NIRS in a resource-poor setting is feasible and has potential as a research tool.